2015
DOI: 10.2176/nmc.ra.2014-0395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Language Function under Awake Craniotomy

Abstract: Awake craniotomy is the only established way to assess patients’ language functions intraoperatively and to contribute to their preservation, if necessary. Recent guidelines have enabled the approach to be used widely, effectively, and safely. Non-invasive brain functional imaging techniques, including functional magnetic resonance imaging and diffusion tensor imaging, have been used preoperatively to identify brain functional regions corresponding to language, and their accuracy has increased year by year. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
(22 reference statements)
0
19
0
2
Order By: Relevance
“…Awake craniotomy has been widely performed in patients with brain lesions in eloquent areas, especially those with glioma, to minimize postoperative brain dysfunction and maximize the extent of tumor resection. [1][2][3][4][5][6] Past studies reported significantly better neurological outcomes and resection extent following awake craniotomy than after general anesthesia in patients with brain lesions in eloquent areas. 2) In patients with glioma, the extent of tumor resection has been reported to be associated with better outcomes, [7][8][9][10] while the development of new perioperative motor or language impairments has been reported to be associated with decreased overall survival, despite no difference in resection extent or adjuvant therapy regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Awake craniotomy has been widely performed in patients with brain lesions in eloquent areas, especially those with glioma, to minimize postoperative brain dysfunction and maximize the extent of tumor resection. [1][2][3][4][5][6] Past studies reported significantly better neurological outcomes and resection extent following awake craniotomy than after general anesthesia in patients with brain lesions in eloquent areas. 2) In patients with glioma, the extent of tumor resection has been reported to be associated with better outcomes, [7][8][9][10] while the development of new perioperative motor or language impairments has been reported to be associated with decreased overall survival, despite no difference in resection extent or adjuvant therapy regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Supl. actividad quirúrgica o intervencionista por excesivo número de facultativos en relación con patología, subespecialización ...), y argumentados por diversos estudios individuales, de comisiones y de Sociedades Científicas con proyecciones a medio y largo plazo en principio convincentes [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . En épocas de déficits de especialistas se ha abogado por lo contrario: aumento de estudiantes de medicina y plazas de residentes, a veces con pocos años de diferencia en el cambio de opinión [36][37][38][39][40][41][42][43][44][45][46][47][48] .…”
Section: Discussionunclassified
“…Indudablemente el mapeo eléctrico intraoperatorio se acepta como el mejor método para obtener información sobre la funcionalidad del tejido subyacente cuando se realiza una cirugía neuro-oncológica 17 . Al evaluar las funciones del lenguaje de los pacientes durante la craneotomía con el paciente despierto, dada la diversidad de factores a tener en cuenta, es necesario seleccionar cuidadosamente las tareas o paradigmas que se realizarán, llevar a cabo rápidamente todos los exámenes y evaluar los resultados a la luz de las condiciones de cada individuo y cada centro 18 .…”
Section: Discusión Y Conclusionesunclassified
“…The role of the language expert includes: preoperative language testing, identification of preoperative symptoms, careful selection of intraoperative tasks, monitoring of whether language is being affected by direct electrical stimulation or resection, management of intraoperative stresses (e.g. discomfort or pain) whilst providing feedback to the surgeon (Kelm et al, 2017, Kanno et al, 2015, Trimble et al, 2015. Intraoperative tests that are sensitive and specific for detection of impairments should be selected based on tasks that use standardised items, are tailored to the lesion site and take into consideration the service user's preoperative level Marien, 2013, Rofes andMiceli, 2014).…”
Section: Introductionmentioning
confidence: 99%